A design strategy for the construction of 2D heteropore covalent organic frameworks based on the combination of C2v and D3h symmetric building blocks. Issue 3 (2nd January 2018) - Qian, Cheng; Liu, En-Cheng; Qi, Qiao-Yan; Xu, Kaijia; Jiang, Guo-Fang; Zhao, Xin
Abstract : A strategy to construct heteropore covalent organic frameworks has been developed based on a desymmetrization design which takes advantage of the combination of C 2v and D 3h symmetries. Abstract : While significant progress in covalent organic frameworks (COFs) has been made in recent years, the construction of COFs with heterogeneous porosity remains a great challenge. In this communication, we report two novel 2D heteropore COFs which bear two kinds of hexagonal micropores with different shapes and sizes. They have been constructed by the condensation of monomers with C 2v - and D 3h -symmetry, and their structures have been confirmed by PXRD studies, synchrotron SAXS experiments, theoretical simulations and pore size distribution analyses.